NEUROPSYCHOLOGICAL BASES OF COMPUTATIONAL ACTIVITY OF THE ELEMENTARY SCHOOL LEARNER: THEORETICAL ASPECTS - Romanyshyn, Ruslana (Mountain School of Ukrainian Carpaty, 2019)
The article deals with the computational activity of elementary school students from the point of view of neuropsychological studies. On their basis, computational activity is attributed to higher mental functions that are inherent only to man and are formed throughout life. The regularities of constructing the process of formation and mastering of knowledge and skills in elementary school students are established. This process is ensured by the work of the cortex of the cerebral hemispheres. The computation, like any higher mental function, is provided by the integrative activity of the entire brain. The value of each part of the brain to the quality of the computational activity can be estimated only from the point of view of neuroscience. The study of local lesions of the brain makes it possible to establish various disorders of mental processes, due to the fallout of certain components of mental activity. Since computational activity, like any other activity, is an integral process, then, when it decays, this integrity is replaced by singularities and fragments. In this case, the activity is violated not only as a chain of actions, but as a hierarchical system. With the impact of individual sections of the brain, computational operations break down according to the laws of its content structure. The research in the field of neuroscience proves that in the case of damage to various parts of the cerebral cortex, only centers of distortion can be established, and not centers of functioning, since a complicated intellectual function cannot be localized in a particular center. It was found that the computation is performed by the joint work of the occipital, parietal and frontal systems of the brain that we will call the system of brain regions that provide computational activity. Moreover, the functional value of a certain area of the cerebral cortex is uneven at different stages of the development of the individual, which is confirmed by the fundamental principle of the dynamic localization of higher mental functions. The essence of this principle is that working units of different zones and levels of the brain, providing a particular mental function may vary in the process of its formation. That is, the function changes in its structure with the development of a person. It also changes in relations with other mental processes, and, consequently, its localization varies, which differs sharply between the child and the adult. Computational operations are complex psychological processes of genesis, structure and flow, and therefore experience the greatest difficulty in teaching children in school.